The Evaluation Of Controller Tracking Performance Based On Taylor’s Series Expansion Model - Maziyah, Mat Noh; M. R., Arshad; Rosmiwati, Mohd Mokhtar (Penerbit Universiti Teknologi Malaysia, 2015)
This paper presents the controller tracking performance of Underwater Glider. The controllers are designed based on linearised model. The equations of motion are restricted to longitudinal plane. The controllers are designed and tested for the glide path moving from 45° to 30° downward and upward. The model is linearised using Taylor’s series expansion linearisation method. The controller developed here is Sliding Mode Control (SMC), and Linear Quadratic Regulator (LQR). The performance of both controllers are compared and analysed. The simulations show SMC produce better performance with about over 30% faster than LQR based its convergence time.